Plants used in Iraqi traditional medicine in Erbil - Kurdistan region - Naqishbandi, Alaadin (Zanco Journal of Medical Sciences (ZJMS), 2014)
Background and objective: Herbal medicine is a traditional or folk medicine practice based on the use of plants’ seeds, berries, roots, leaves, barks, flowers and plant extracts for medicinal purposes. This survey highlights the traditional phytotherapy practices by traditional healers of Erbil-Kurdistan region in the treatment of various disorders. Methods: An ethnobotanical survey was undertaken to collect information from traditional healers on the use of medicinal plants in Erbil-Kurdistan region. The indigenous knowledge of local traditional healers and the native plants used for medicinal purposes were collected through questionnaire and personal interviews. Results: The investigation revealed that the traditional healers were not professionally authorized and 32 plants belonging to 23 families were used to treat various diseases in traditional medicine. The plants reported have been identified and presented in a table with the vernacular names, useful parts, dosage preparations and medicinal uses. Conclusion: Many recorded species of plants are used in Erbil- Kurdistan region in traditional medicine but lack phyto-therapeutic evidence. Most indigenous plants remain to be studied which may yield many exciting data for further investigation.